New 2D integrable families with a quartic second invariant - Yehia, H.M. (Механика твердого тела, 2011)
The method introduced by the present author in 1986 still proves most effective in constructing integrable 2-D Lagrangian systems, which admit in addition to the energy another integral of motion that is polynomial in velocities. In a previous article (J. Phys. A: Math. Gen., 39, 5807– 5824, 2006) we constructed a system, which admits a quartic complementary integral. This system, called by us “master”, is the largest known, as it involves 21 parameters, and contains, as special cases of it, almost all previously known systems of the same type that admit a quartic integral. In the present note we generalize the method we used before to construct new severalparameter systems that are not special cases of the master system. A new system involving 16 parameters is introduced and a special case of it admits interpretation in a problem of rigid body dynamics. It gives a unification of certain special versions of known classical integrable cases due to Kovalevskaya, Chaplygin and Goriatchev and other cases recently introduced by the present author. Продолжены исследования, начатые автором в 1986 году, и посвященные изучению условий существования у лагранжевых систем первых интегралов четвертого порядка. Рассматриваемая система характеризуется 16 параметрами. Получена структура лагранжиана, для которой дифференциальные уравнения движения допускают решения, характеризующиеся первым полиномиальным интегралом четвертого порядка. Это позволило обобщить известные случаи интегрируемости Ковалевской, Чаплыгина и Горячева классической задачи о движении твердого тела, имеющего неподвижную точку. Продовжено дослiдження, початi автором у 1986 роцi, i присвяченi вивченню умов iснування у лагранжевих систем перших iнтегралiв четвертого порядку. Розглядувана система характеризується 16 параметрами. Одержано структуру лагранжиана, для якої диференцiальнi рiвняння руху припускають розв’язки, що характеризуються першим полiномiальним iнтегралом четвертого порядку. Це дозволило узагальнити вiдомi випадки iнтегровностi Ковалевської, Чаплигiна i Горячева класичної задачi про рух твердого тiла, яке має нерухому точку.